THE INFLUENCE OF ENGLISH ON MODERN UZBEK ADVERTISING LANGUAGE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In today’s globalized world, English has emerged as a leading medium of communication, particularly within media, business, and advertising. The influence of English is strongly evident in Uzbekistan’s advertising sector, shaped by international marketing trends, cultural interaction, and technological advancement. This paper examines how English affects the linguistic and sociocultural landscape of contemporary Uzbek advertising, focusing on the factors driving the increasing incorporation of English words and phrases, their impact on consumer attitudes, and the significance of bilingualism in the development of modern advertising strategies.